MENINGKATKAN PRESTASI BELAJAR IPS DENGAN MODEL PEMBELAJARAN STAD (Student Team Achivement Division)PADA SISWA KELAS III SD NEGERI 4 NGRAHO KEDUNGTUBAN BLORA - Sutrisno . (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
The purpose of this study was aimed to improve learning achievement IPS with Learning Model STAD (Student Team Achievement Division) in the third gradestudents of SD Negeri 4 Ngraho Kedungtuban Blora. This research is a classroom actionresearch subjects Class III students of SD Negeri 4 Ngraho Kedungtuban Blora totaling16 people, consisting of nine boys and seven girls. The procedure of this study uses fourphases, namely planning, action, observation and reflection. Data collection techniquesin this study using data collection instruments in the form of guidelines for observation,testing guidelines, documentation and interview guides. Data analysis techniques in thisstudy using the average and the percentage of completeness. The study concluded that:Learning social studies learning model STAD (Student Team Achievement Division) inthe Class III SD Negeri 4 Ngraho Kedungtuban Blora, can improve studentachievement. The increase in the percentage of students learning seen from theincreasing average value of students and the percentage of completeness. Prasiklusaverage learning outcomes 64.37 with the percentage of completeness 31%. I cycleaverage of 65.28 with the percentage of learning outcomes completeness 56%. Cycle IIaverage learning outcomes 83.43 with the percentage of completeness of 87.5%.Keywords: Learning STAD (Student Team Achievement Division), IPS LearningAchievement.